HIV and syphilis among men who have sex with men and transgender individuals in China: a scoping review. (October 2016) - Tang, Songyuan; Tang, Weiming; Meyers, Kathrine; Chan, Polin; Chen, Zhongdan; Tucker, Joseph D
Abstract: Background: HIV and syphilis epidemics in men who have sex with men (MSM) continue to grow in China, despite considerable government attention. We did a literature review to synthesise key features of the HIV and syphilis epidemics and responses among MSM and transgender individuals in China. Our goal was to inform evidence-based recommendations for policy makers and program managers. Methods: We searched Medline, EMBASE, the Cochrane Library, China National Knowledge Infrastructure, and Wanfang using the terms "MSM", "transgender", "meta-analysis", "review", and "China" for articles published in the last six years. Articles focused on HIV and syphilis prevalence and interventions among MSM and transgender individuals in China. We defined linkage to care as having an HIV doctor's appointment within six months of diagnosis and retention in care as two doctor visits each year. We contacted experts to identify additional supplemental articles, unpublished literature, government reports, policy documents, and best practice guidelines if data of interest were not available in systematic reviews. Findings: Overall, HIV prevalence among Chinese MSM was approximately 8% in 2015, with a three-times higher prevalence observed in five provinces of southwest China. Transgender individuals are not identifiable from national HIV, sexually transmitted disease, or other sexual health surveillance systems. Limited data is shared between public health authorities and community-based organisations. As in other low and middle-income countries, China has low rates of HIV testing, linkage to care, and retention. Community-based sexual health programs such as collaborations between Centers for Disease Control and community-based organisations have been effective in promoting HIV self-testing among MSM. One randomised controlled trial (NCT02248558 ) showed that crowdsourcing contests were effective compared to social marketing for promoting HIV testing among MSM and transgender individuals in China. Interpretation: Our report informs the following recommendations for policy makers and program managers: increase data sharing between community-based organisations and local Centers for Disease Control, use online surveys to capture data from MSM and transgender individuals who do not disclose their sexual orientation to healthcare professionals, expand HIV self-testing programs among MSM and transgender individuals, use crowdsourcing contests and social media to promote HIV services, improve engagement and participation among community-based organisations. Funding: US National Institute of Allergy and Infectious Diseases (NIAID; 1R01AI114310); University of North Carolina (UNC)-South China Sexually Transmitted Disease Research Training Centre (Fogarty International Centre (FIC); 1D43TW009532); UNC Center for AIDS Research (NIAID; 5P30AI050410); the UNC Chapel Hill, Johns Hopkins University, Morehead School of Medicine and Tulane University (UJMT) Fogarty Fellowship (FIC; R25TW0093); WHO-China